Kröller-Müller; Honderd jaar bouwen en verzamelen. - Hammacher, A.M.; Kröller-Müller Museum, Otterlo; Oxenaar, R.W.D.; Wolk, J. van der (Haarlem : Joh. Enschedé en Zonen, 1988)
Aeschbacher, Hans ; Andre, Carl ; Anselmo, Giovanni ; Armando ; Arp, Hans (Jean) ; van Bakel, Gerrit ; Berlage, Hendrik P. ; Beuys, Joseph ; Bijhouwer, J.T.P. ; Boccioni, Umberto ; Buisman, Sjoerd ; Buren, Daniel ; Caro, Anthony ; César ; Chadwick, Lynn ; Christo ; Colla, Ettore ; Deacon, Richard ; Dekkers, Ad ; Denis, Maurice ; Dibbets, Jan ; Dodeigne, Eugène ; Dubuffet, Jean ; Duchamp-Villon, Raymond ; van Elk, Ger ; Ensor, James ; Epstein, Jacob ; Fabro, Luciano ; Flanagan, Barry ; Riverhead (New York) ; Freundlich, Otto ; Gauguin, Paul ; Giacometti, Alberto ; Gilbert & George ; van Gogh, Vincent ; González, Julio ; Graham, Dan ; Gris, Juan ; Finlay, Ian Hamilton ; Haraguchi, Noriyuki ; Hepworth, Barbara ; Hesse, Eva ; Judd, Donald ; Kelly, Ellsworth ; Kemps, Niek ; King, Phillip ; Kirkeby, Per ; Knoebel, Imi ; Kobro, Katarzyna ; de Kop, David van ; Kounellis, Jannis ; van der Leck, Bart ; Leger, Fernand ; LeWitt, Sol ; Lipchitz, Jacques ; Long, Richard ; Maillol, Aristide ; Manzoni, Piero ; Marini, Marino ; Mark, Arno Van der ; Martin, Henri Etienne ; Martini, Arturo ; Mastroianni, Umberto ; Mendes da Costa, Joseph ; Merz, Mario ; Mogami, Hisayuki ; Mondriaan, Piet ; Monet, Claude ; Moore, Henry ; Morellet, François ; Morris, Robert ; Nauman, Bruce ; Nevelson, Louise ; Noguchi, Isamu ; Nordman, Maria ; O'Brien, Robert ; Oldenburg, Claes ; Oppenheim, Dennis ; van Pallandt, Charlotte ; Pan, Marta ; Panamarenko ; Penalba, Alicia ; Penck, A.R. ; Penone, Giuseppe ; Picasso, Pablo ; Pistoletto, Michelangelo ; Rädecker, John ; Redon, Odilon ; Renoir, Auguste ; Richier, Germaine ; Rickey, George ; Rietveld, Gerrit ; Van Rijsselberghe, Theo ; Rodin, Auguste ; Rogge, Cornelius ; Rosso, Medardo ; Rückriem, Ulrich ; Ruthenbeck, Reiner ; Saito, Yoshishige ; etc.
boek